Quantity of dietary protein intake, but not pattern of intake, affects net protein balance primarily through differences in protein synthesis in older adults - Kim, Il-Young; Schutzler, Scott; Schrader, Amy; Spencer, Horace; Kortebein, Patrick; Deutz, Nicolaas E. P.; Wolfe, Robert R.; Ferrando, Arny A. (American journal of physiology: endocrinology and metabolism, 2015)
To examine whole body protein turnover and muscle protein fractional synthesis rate (MPS) following ingestions of protein in mixed meals at two doses of protein and two intake patterns, 20 healthy older adult subjects (52–75 yr) participated in one of four groups in a randomized clinical trial: a level of protein intake of 0.8 g (1RDA) or 1.5 g·kg −1 ·day −1 (∼2RDA) with uneven (U: 15/20/65%) or even distribution (E: 33/33/33%) patterns of intake for breakfast, lunch, and dinner over the day (1RDA-U, 1RDA-E, 2RDA-U, or 2RDA-E). Subjects were studied with primed continuous infusions of l-[ 2 H 5 ]phenylalanine and l-[ 2 H 2 ]tyrosine on day 4 following 3 days of diet habituation. Whole body protein kinetics [protein synthesis (PS), breakdown, and net balance (NB)] were expressed as changes from the fasted to the fed states. Positive NB was achieved at both protein levels, but NB was greater in 2RDA vs. 1RDA (94.8 ± 6.0 vs. 58.9 ± 4.9 g protein/750 min; P = 0.0001), without effects of distribution on NB. The greater NB was due to the higher PS with 2RDA vs. 1RDA (15.4 ± 4.8 vs. −18.0 ± 8.4 g protein/750 min; P = 0.0018). Consistent with PS, MPS was greater with 2RDA vs. 1RDA, regardless of distribution patterns. In conclusion, whole body net protein balance was greater with protein intake above recommended dietary allowance (0.8 g protein·kg −1 ·day −1 ) in the context of mixed meals, without demonstrated effects of protein intake pattern, primarily through higher rates of protein synthesis at whole body and muscle levels.